1999
DOI: 10.1021/la980540y
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Methylphosphonic Acid with the Surface of Goethite Particles in Aqueous Solution

Abstract: Adsorption of methylphosphonic acid (MPA) onto goethite (α- FeOOH) was studied as a function of pH and the concentration of MPA in solution. In situ attenuated total reflectance-FTIR (ATR-FTIR) techniques were used to identify the type of surface complexes formed under each of the solution conditions used in the adsorption studies. Additionally, electrophoretic mobility measurements were performed in each of these systems. At low pH and high Γ, MPA was bound to the surface of goethite predominantly as a monode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 13 publications
12
72
1
Order By: Relevance
“…The frequency values of the P=O and P-OX vibration are altered by the adsorption form. Barja and others reported that the adsorption form is constrained by the adsorption density, where bridging bidentate complexes can transform to protonated monodentate complexes with increasing the adsorption density [43]. Similarly, the broadening of the bands should be partly ascribed to the multiple adsorption forms at the CeNPs surface in the present experiments.…”
Section: Icp-ms Ic Icp-ms Icsupporting
confidence: 57%
“…The frequency values of the P=O and P-OX vibration are altered by the adsorption form. Barja and others reported that the adsorption form is constrained by the adsorption density, where bridging bidentate complexes can transform to protonated monodentate complexes with increasing the adsorption density [43]. Similarly, the broadening of the bands should be partly ascribed to the multiple adsorption forms at the CeNPs surface in the present experiments.…”
Section: Icp-ms Ic Icp-ms Icsupporting
confidence: 57%
“…Phosphate groups originating from phospholipids, DNA, LPS, and other extracellular biomolecules provide potential binding sites to initiate bacterial adhesion to metal oxide surfaces. The binding of phosphate with Fe oxide surfaces is well documented in numerous ATR-FTIR spectroscopic studies (Barja et al, 2001(Barja et al, , 1999Cagnasso et al, 2010;. used a combined ATR-FTIR spectroscopy and modeling approach to demonstrate the occurrence of P-O-Fe bonds (1037 cm −1 ) for extracted EPS reacted with goethite (α-FeOOH) (Figure 1.16).…”
Section: Bacteria and Biomolecule Adhesionmentioning
confidence: 98%
“…Coordination of the phosphonate group with aqueous Fe was indicated by a broad and unresolved band from 1200 to 950 cm −1 where stretching vibrations of the PO 2 − and PO 3 − are observed in the free ligand, and the absence of P=O and P-OH at 1400-1200 cm −1 and 917 cm −1 , respectively (Barja and dos Santos Afonso, 1998). Barja et al (1999) employed methylphosophonic acid (MPA) as an adsorbate surrogate for glyphosate in adsorption studies with goethite. In situ CIR-FTIR spectra at low pH suggested that protonated MPA was bound through a monodentate complex between the phosphonate group and the goethite surface; whereas, a bridging bidentate complex was the proposed structure for MPA bonding at high pH.…”
Section: Herbicides and Pharmaceuticalsmentioning
confidence: 99%
“…In the case of goethite, (g-AlOOH), it was found that methylphosphonic acid bound to the surface as a monodentate or a bidentate species depending on the pH and the concentration [163].…”
Section: Hybrid Organic-inorganic Materials Based On Organophosphorusmentioning
confidence: 99%